CONSUMER ACCEPTANCE OF JERKYMINCED AFRICAN CATFISH (Clarias gariepinus) MEAT MIXED WITH SAGO FLOUR - Aisyah, Siti; ', Suparmi; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to determine the consumer acceptance of jerky minced African catfish (Clarias gariepinus) meat mixed with varied amounts of sago flour. This research was conducted by using the experiment method. The treatments were the mixing of minced fish meat with sago flour at different amounts, namely: D0 (100 g of tapioca as a control, D1 (50 g of sago flour), D2 (100 g of sago flour), and D3 (150 g of sago flour). The results showed that the mixing with 50 g sago flour (D1) was producing the highest consumer acceptance of the jerky catfish meat The organoleptic characteristics of the product was showing the light brown and savory color, tasty, balanced spice taste, torn and chewy texture, and have typical aroma of spices. It contained 41.6% moisture, 2.23% ash, and 20.98% protein.Key words: consumer acceptance, Clarias gariepinus, jerky meat, sago flour